Capricorno Alae VII Phrygum … (i) Interim report on the fort near Tel Shalem. (2019) - Arubas, Benjamin; Heinzelmann, Michael; Mevorah, David; Overman, Andrew
Abstract : A multi-disciplinary research project has been begun in the fields next to the site of Tel Shalem (fig. 1), the locus of important discoveries since the 1970s (primarily the bronze statue of Hadrian). Recent geophysical prospections have detected the clear layout of a Roman fort and possibly even two successive forts. Two short excavation seasons carried out in 2017 and 2019, with a focus on the principia, resulted in finds that shed new light on the nature, history and identity of the site.